Monetary Policy in an Inside-Money, Open Economy: Reply - Mathieson, Donald J. (Quarterly Journal of Economics, 1981)
Journal Article Monetary Policy in an Inside-Money, Open Economy: Reply Get access Donald J. Mathieson Donald J. Mathieson International Monetary Fund Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 96, Issue 2, May 1981, Pages 357–361, https://doi.org/10.2307/1882396 Published: 01 May 1981